12. CLINICAL AND ULTRASONOGRAPHIC FEATURES OF PATIENTS WITH KNEE OSTEOARTHRITIS IN STAGES 0-2 ACCORDING TO KELLGREN-LAWRENCE (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical characteristics and ultrasound imaging features of patients with knee osteoarthritis in stage 0 to stage 2 according to Kellgren - Lawrence at Can Tho Central General Hospital.Subjects and methods: A cross-sectional descriptive study was conducted on 69 patients diagnosed with KOA according to ACR (1991) from March 2023 to December 2023.Results: The average age of patients was 65.3 ± 8.5 years, with females accounting for 91.3%. The prevalence of KOA in stages 0, 1 and 2 according to Kellgren - Lawrence on X-ray was 6.8%, 46.6% and 46.6%, respectively. The most common clinical symptoms were joint pain (100%), limited range of motion (100%), joint crepitus (92.7%), joint effusion (55.1%), and joint leakage signs (94.2%). The mean VAS pain score was 4.56 ± 1.01, and the mean WOMAC score was 48.51 ± 10.32. Regarding ultrasound imaging, 91% of patients had osteophytes, 90.2% had cartilage damage, 54.1% had joint effusion and 11.3% had Baker’s cysts.Conclusion: All patients experienced joint pain and limited range of motion, with an average VAS pain score of 4.56 ± 1.01 and an average WOMAC score of 48.51 ± 10.32. Knee ultrasound is capable of detecting lesions in osteoarthritis, especially early osteoarthritis.
Keywords: Knee osteoarthritis; knee ultrasound.